Optimization Strategies for Government Asset Management in Jakarta Using Multi-Criteria Analysis - Sidik Nur Toha; Ahmad Ghiffari; Feirully Irzal (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The large number of government assets is often not managed properly, thus becoming a financial burden for the government, including the DKI Jakarta Provincial Government. On the other hand, the government has limitations in managing their assets. Therefore, cooperation in asset management and optimization is important to support the increase in local revenue. It is crucial to map government-owned assets so that they can be utilized in accordance with the highest and best use principle. This research uses data from 31 samples of Jakarta government asset data to map assets, focusing on land and buildings, using multiple criteria analysis. These criteria are compiled based on expert judgment and weighted using the analytical hierarchy process method. The results show that there are 6 assets in the high market category and high condition, 7 assets in the high market category but low condition, 8 assets in the low market category but high condition, and 9 assets in the low market category and low condition.